SUBSTANTIVISCHES ATTRIBUT IM PRÄPOSITIONALKASUS DES DEUTSCHEN UND IHRE ENTSPRECHUNGEN IM TÜRKISCHEN - Aygün, Mehmet (Selcuk University, 2006)
In this study, the prepositional constructions in German and Turkish were dealt with and explained with examples. The usage differences were also discovered on that subject because German and Turkish belong to different language families. It was seen that the prepositional constructions could be used as possessive constructions, be replaced with the relative clauses, but be used more economically and practically than these, and also enriched the meaning. It was also found out that the prepositions, various noun conditions, and the word formation endings substituted for the prepositional constructions in German

Bu çalışmada, Almanca ve Türkçe’deki edatlıtamlamalar ele alınarak örneklerle açıklandı. Almanca ve Türkçe farklıdil ailelerine mensup olduklarından, bu konuda da kullanım farklılıklarıortaya çıktı. Edatlıtamlamaların isim tamlamalarıgibi kullanılabildikleri, ilgi cümlecikleriyle karşılanabildikleri, fakat bunlardan daha ekonomik ve pratik kullanıldıklarıve ifadeye zenginlik kattıklarıgörüldü. Almanca’daki edatlıtamlamaların, Türkçe’de edatlar, değişik isim durumlarıve kelime türetme ekleriyle karşılandığıtespit edildi.